Consent requires a relationship: rethinking group consent and its timing in ethnographic research. Issue 6 (1st November 2020) - Nairn, Karen; Showden, Carisa R.; Sligo, Judith; Matthews, Kyle R.; Kidman, Joanna
ABSTRACT: Activist groups in ethnographic research re-negotiated our Ethics Committee's expected order of securing consent before data collection, demonstrating the importance of researchers taking time to build relationships first. Although the Ethics Committee expected us to obtain group consent, the literature provides little guidance on how to do this. We developed a Memorandum of Understanding to summarize what forms of participant observation each group agreed to and how we would reciprocate. In this article, we (re)conceptualize consent, using analogies to consent in social contract theory and sexual relations to offer a critical perspective on what constitutes consent. We argue that taking time to build relationships before expecting research participants to consent and replacing informed consent with a negotiated agreement is a more ethical approach. We advocate for Ethics Committees to expand the meaning of 'informed consent' and review its timing, especially for ethnographic research with groups.